Correlation of metabolic parameters, neurotrophin-3, and neurotrophin-4 serum levels in women with schizophrenia and first-onset depression. (17th February 2019) - Skibinska, Maria; Kapelski, Pawel; Rajewska-Rager, Aleksandra; Szczepankiewicz, Aleksandra; Narozna, Beata; Duda, Joanna; Dmitrzak-Weglarz, Monika; Twarowska-Hauser, Joanna; Pawlak, Joanna
Abstract: Background: Neurotrophin-3 (NTF3) and neurotrophin-4 (NTF4) play a crucial role in the neurodevelopment, differentiation, survival, and protection of neurons in different brain regions. Schizophrenia and depression are highly associated with metabolic abnormalities. Longitudinal and cross-sectional comparisons of NTF3 and NTF4 levels, as well as clinical and metabolic parameters, were studied in schizophrenia, first-episode depression, and control groups. Materials and methods: Serum NTF3 and NTF4 levels, body mass index (BMI), fasting serum glucose and lipid profile: cholesterol, triglyceride, high-density lipoprotein (HDL-C) and low-density lipoprotein (LDL-C) were measured at baseline and week 8 in 133 women: 55 patients with schizophrenia (19 with first-episode and 36 chronic), 30 patients with a first-episode depression and 48 healthy controls. The severity of the symptoms was evaluated with the Positive and Negative Syndrome Scale, 17-item Hamilton Depression Rating Scale and the Beck Depression Inventory. Results: Longitudinal and cross-sectional comparisons did not detect any differences in the serum levels of NTF3 and NTF4 between studied groups. NTF3 and NTF4 levels were strongly correlated. Correlation of NTF3 and HDL-C levels at baseline was observed. Significant changes in cholesterol and fasting serum glucose levels in first-episode depression patients during 8 weeks of treatment were detected. Significant differences in BMI and LDL-C levels between schizophrenia and first-episode depression patients were discovered. Conclusions: To our knowledge, this is the first research which correlates NTF3 and NTF4 with metabolic parameters. Our study does not support the theory that the peripheral levels of NTF3 and NTF4 are disturbed in schizophrenia or first-episode depression.